Rancang Bangun Sistem Detektor Gas Nh3 Pada Peternakan Broiler Berbasis Arduino - Ali, Baso; Muhamin, Muhaimin (Journal Software, Hardware and Information Technology, 2024)
This research aims to create an electronic circuit to detect ammonia gas levels using the MQ-135 sensor, making it easier for farmers to detect ammonia gas levels, which can hinder the growth of broiler chickens if too high. The research was conducted at the Karang-karangan Village Broiler Chicken Farm. This type of research uses Research and Development (R&D) for the manufacture and design of ammonia gas detection equipment on farms. The application of the ammonia gas detector consists of several steps: data collection, system analysis, design, manufacture, and system testing. The problem that occurs in broiler farms is farmers' ignorance of ammonia gas levels before spraying. The research results show that the detection tool can be used well, and farmers can easily operate it. Farmers must first find out the ammonia gas levels on the farm before spraying disinfectant, and if the sensor detects levels exceeding the normal safe limit, the buzzer will sound and display the value on the LCD screen.